Manufacturing polymer/clay nanocomposites through elongational flow technique. Issue 12 (10th September 2017) - Huang, Zhao-Xia; Meng, Cong; Zhang, Guizhen; Qu, Jin-Ping
ABSTRACT: A novel processing technique that employs continuous elongational flow to fabricate polymer/clay nanocomposites has been developed and evaluated in this work. A self-made vane mixer has been used to supply the continuous elongational flow, while high-density polyethylene (HDPE) and organic montmorillonite (O-MMT) were used as the polymer matrix and clay, respectively. The morphology of resultant nanocomposites has been carefully revealed and studied by examining wide-angle X-ray diffraction (WAXD) and transmission electron microscopy (TEM). Intercalation effect and dispersion of O-MMT layers have been investigated by the morphology study. The results indicate that the elongational flow has a great potential in melt intercalation of O-MMT, and can lead to an orderly O-MMT layers' distribution. Thermal properties of as-mixed nanocomposites that prepared under elongational flow have been determined by the differential scanning calorimetry (DSC), which demonstrates that the introduction of O-MMT nano-sheets is bad for the crystal of HDPE matrix. The universal tensile test shows how O-MMT layers affect the mechanical properties of nanocomposites, including the tensile strength and elongation at break. The strain–stress relationship reveals that with continually adding O-MMT layers, the tensile strength increases at first, and then decreases. While the elongation at break shows the same trend.